Investigating the changes in the levels of HbA1c, blood fat and insulin sensitivity in elder patients with type II diabetes mellitus due to combined medication of pioglitazone and melbine and single-use of pioglitazone - Sun, Yuanyuan; Yu, Qigui; Xie, Jun (Cellular and Molecular Biology, 2020)
This study was founded for the purpose investigate the differences in effects of combined medication of pioglitazone and melbine and single-use of pioglitazone on the levels of hba1c, blood fat and insulin sensitivity of elder patients with type II diabetes mellitus (T2DM), to provide clinical reference and guidance for the treatment of T2DM in elder patients. For this purpose, we selected a total of 120 elder patients with T2DM who visited the clinic or were admitted to this hospital between July 2016 and July 2017 and divided them into the observation group and the control group (n=60 for each group). For the control group, they only took pioglitazone for treatment, while those in the observation additionally took melbine for treatment. Then, we observed the levels of FPG, 2hPG, HbA1c, blood fat, FINS, 2hINS and HOMA-IR. Results showed that after treatment, significant decreases were seen in levels of FPG, 2hPG and HbA1c in patients of two groups compared to the levels before treatment, and the levels in the observation group decreased more evidently than those in the control group (p<0.05); besides, the levels of total glyceride, total cholesterol and LDL-C were all significantly lower than those before treatment, with an elevated HDL-C, and those levels of TG, TC and LDL-C in the observation group were significantly lower than those in the control group; the level of HDL-C was higher than the control group (p<0.05). Similar decreases were identified in the levels of FINS, 2hFINS and HOMA-IR after treatment (p<0.05), and the levels in the observation group were also significantly lower than those in the control group (p<0.05). In the observation group, the incidence rate of adverse reactions was 10% (6/60), while in the control group was 8.33% (5/60), but the difference between the two groups showed no statistical significance (p>0.05). It is concluded that combined medication of pioglitazone and melbine can effectively reduce the levels of plasma glucose, blood fat and the HOMA-IR, with an elevated sensitivity to insulin, but no severe adverse reactions, manifesting a promising safety in long-term administration. It is worthy of being promoted in clinical practice.